2005
DOI: 10.1093/ndt/gfk011
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional-inflammation status and resistance to erythropoietin therapy in haemodialysis patients

Abstract: Our findings support a clear association between EPO responsiveness and nutritional and inflammation variables in haemodialysis patients; iron deficiency is still a major cause of hypo-responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
127
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 15 publications
6
127
2
6
Order By: Relevance
“…Comorbidities are thought to increase inflammatory state and hence associated with poor response to Epo [50,51]. The current study did not demonstrate a link between presence of hypertension, diabetes mellitus, congestive heart failure and ERI.…”
Section: Individual Response Variations To Erythropoietin Stimulatingcontrasting
confidence: 73%
See 1 more Smart Citation
“…Comorbidities are thought to increase inflammatory state and hence associated with poor response to Epo [50,51]. The current study did not demonstrate a link between presence of hypertension, diabetes mellitus, congestive heart failure and ERI.…”
Section: Individual Response Variations To Erythropoietin Stimulatingcontrasting
confidence: 73%
“…Previous studies have shown that inflammation is one factor that reduces the response to Epo [6,50,63,64]. In addition, nutritional status plays a fundamental role in the clinical course of HD patients…”
Section: Individual Response Variations To Erythropoietin Stimulatingmentioning
confidence: 99%
“…This finding seems to be true in clinical practice; in hemodialysis patients, a lower serum albumin level is associated with ESA hyporesponsiveness (19).…”
Section: Introductionmentioning
confidence: 77%
“…Among these factors, iron stores are most thoroughly described (7)(8)(9)(10)(11). Other factors include inflammation (12,13), adequacy of dialysis (14,15), nutritional status (16), and hyperparathyroidism (17).…”
mentioning
confidence: 99%